PENYULUHAN DAN PENGUATAN KEYAKINAN PETANI DALAM PENERAPAN PERTANIAN ORGANIK UNTUK KEBERLANJUTAN DAN KESEJAHTERAAN - Arifin, Zainal; Apzani, Wawan; Zainab, Siti; Wardhana, Agung Widya; Baharuddin; Sunantra, I Made; Hasanah, Mirfatul; Haryantin, Baiq Azizah (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The "Baru Sadar" farmer group in Gerantung village, Central Lombok, NTB, has received training in organic farming, but still has doubts about its effectiveness, especially in terms of crop yields. This uncertainty is related to the productivity of organic farming compared to conventional methods, so they have not fully converted to an organic farming system. Extension was used to improve their understanding of organic practices, increase knowledge, identify problems and offer solutions to increase farmers' confidence in the results of the organic system. The methods used included lectures, question and answer sessions and in-depth discussions with group leaders and extension officers. Extension materials covered the importance of organic farming, soil management, organic fertiliser and the business of organic products such as certification and marketing. The farmer group members were enthusiastic and raised several issues during the discussion, such as slow plant growth with organic fertiliser, low productivity and marketing constraints. Continued extension support, financial assistance, demonstration plots and marketing facilitation are needed to encourage farmers to switch to more sustainable practices so that more farmers are motivated to adopt organic farming systems.